Celebrating Adam Watkins' 6th Birthday - Watkins, Howard::::::::: (1984)
Adam Watkins sleeping on twin bed Howard Watkins used as a child Wall poster of penguins jumping off of ice edge; Adam's Indian Guides beaded necklace on wall